Physical, chemical and microbiological analysis of bottled water in Pokhara, Nepal - Maskey, Manisha; Annavarapu, Laxminarasimha Sharma; Prasai, Tista; Bhatta, Dharma Raj (Journal of Chitwan Medical College, 2020)
Background: Today possibility of rendering water non-potable by various types of contaminants (physical, chemical and biological) is of considerable importance. It is not only the microbial contaminants but also the physical and chemical contaminants, playing an important role in compromising our health in many ways. The aim of this study was to assess the physical, chemical and the microbiological quality of commercially produced bottled water in Pokhara city. Methods: A study was conducted to assess the quality of bottled drinking water produced in Pokhara city. Total of 21 brands of bottled water was collected, first batch in monsoon season and second batch in pre-monsoon season, from the market. The physical, chemical and microbial assessment was carried out as per National Drinking Water Quality Standards, 2062. Coefficient of variation and t-test were applied where applicable. Results: Better water quality was found in Pre-monsoon season than that of monsoon season, in regard to microbial assessment. None of the samples in first batch tested positive for coliform whereas in second batch 38.2% of samples tested positive for coliform. Coefficient of variation for pH and chloride content was, 8.9% and 6.1%, 35.6% and24.19%, in pre-monsoon and monsoon season respectively. Both were found to be statistically significant. While other tested parameters were within normal limits. Conclusions: The quality bottled drinking water available for sale do not meet the standards given by National Drinking Water Quality Standards, particularly the microbial quality.